A comparison of chinese and colombian university efl students regarding learner autonomy (2015)
This research seeks to gain deeper understanding of learner autonomy in English as a Foreign Language students from different cultures through the identification and analysis of similarities and differences between Chinese and Colombian students from two public universities: Tianjin Foreign Studies University in China and Universidad Surcolombiana in Colombia. Data were gathered using questionnaires and interviews for comparative research. The participants’ responses were analyzed using quantitative methods such as independent samples t-test and qualitative methods such as data codification and triangulation were also used. The results indicate a significant difference between the two groups of learners regarding their autonomy. Complementarily, their autonomy-enhancement difficulties were diagnosed.Esta investigación busca obtener un mejor entendimiento acerca de la autonomía de los aprendices de inglés como lengua extranjera provenientes de diferentes culturas, mediante la identificación y el análisis de las diferencias y similitudes entre estudiantes chinos y colombianos pertenecientes a dos universidades públicas: Universidad de Estudios Extranjeros de Tianjin en China y la Universidad Surcolombiana de Colombia. Los datos se recolectaron usando cuestionarios y entrevistas para una investigación de tipo comparativo. Las respuestas de los participantes se analizaron utilizando métodos cuantitativos tales como prueba T para muestras independientes; al igual que métodos cualitativos como codificación y triangulación. Los resultados indicaron que hay una diferencia significativa en la autonomía de los dos grupos de aprendices. Además, se diagnosticaron las dificultades que ellos presentan en el mejoramiento de su autonomía.